Pemanfaatan Media Video Pada Website Dan Youtube Untuk Meningkatkan Kemampuan Toefl Dan Menulis Abstrak Kti Calon Lulusan Unived - Azizatul Banat; Eli Diana; Mariska Febrianti; Filza Ratu Nabila; Wahyu Dirgantara; Putri Mardanis (Universitas Dehasen Bengkulu, 2024)
TOEFL is a Test of English as a Foreign Language which is a test of basic English language skills which is also one of the requirements for prospective graduates at the University of Dehasen Bengkulu. In the last few years after the Covid 19 pandemic, the TOEFL test as a graduation requirement at the University of Dehasen Bengkulu was carried out using Google Forms and information media such as websites and YouTube as intermediary media in conveying important material to prospective graduates. Apart from that, prospective graduates need to be provided with material about the importance of Scientific Writing abstracts which are related to the student's final assignment, namely the thesis. The thesis’s abstract is translated into English at UPT Bahasa Inggris to make it easier for readers to search for research reference titles through the abstract. Apart from this aim, the title of the scientific writing abstract at the University of Dehasen Bengkulu, will be translated as a reference for the thesis title in the English transcript. In the context of community service carried out by a team of lecturers from the Faculty of Teacher Training and Education who collaborated with the UPT English Language Team at the University of Dehasen Bengkulu as managers and organizers of TOEFL and Thesis’s abstract translation which raised the title